Unconventional Sea Surface Temperature Regime Around Japan in the 2000s–2010s: Potential Influences on Major Fisheries Resources - Kuroda, Hiroshi; Saito, Toshihiko; Kaga, Toshiki; Takasuka, Akinori; Kamimura, Yasuhiro; Furuichi, Sho; Nakanowatari, Takuya (Frontiers in Marine Science, 2020)
Climate-change associated changes in oceanographic conditions, particularly sea surface temperatures (SSTs), have systematically affected many marine fisheries resources around Japan. The Pacific Decadal Oscillation (PDO) index is considered one of the most important climate indices for describing basin-scale SST variations in the North Pacific, which are closely related to decadal variations in fisheries resources. Time series of the PDO index has been used to conventionally classify decadal conditions of ocean and fisheries resources around Japan as either warming or cooling regimes. It is now clear that for the 2000s to the mid-2010s, mostly during the “global surface warming slowdown,” the SST regime around Japan was unconventional; despite the PDO index being in a negative phase, which normally corresponds to a warming regime around Japan, SSTs exhibited decadal cooling in some waters and seasons. SSTs in the western part of the North Pacific subtropical gyre gradually decreased, particularly in autumn–spring, whereas SSTs in the western subarctic gyre and the Sea of Okhotsk increased. Moreover, SSTs between the subtropical and subarctic waters around northern Japan exhibited seasonal contrasts that were decadally intensified through the combined effects of cooling in winter–spring and warming in summer–autumn. Some major marine fisheries resources around Japan showed decadal increases or decreases beginning in the mid-2000s, and appeared to respond to the unconventional SST changes in their early life stages. In this paper, we review atmosphere and ocean conditions around Japan in the 2000s–2010s in terms of global climate, present an overview of potential impacts of decadal SST trends on five major commercial fisheries resources (walleye pollock, chum salmon, Japanese sardine, Japanese anchovy, and Japanese flying squid), and raise awareness that an unconventional regime can appear transiently during a state of global warming.